Steroids from Marine-Derived Fungi: Evaluation of Antiproliferative and Antimicrobial Activities of Eburicol - Ana Camila Dos Santos Dias; Aurélie Couzinet-Mossion; Nicolas Ruiz; Fatima Lakhdar; Samira Etahiri; Samuel Bertrand; Lucie Ory; Christos Roussakis; Yves François Pouchus; El-Hassane Nazih; Gaetane Wielgosz-Collin (Marine Drugs, 2019)
The most common sterol in fungi is ergosterol, which has frequently been investigated in human pathogenic fungal strains. This sterol, and others isolated from fungal strains, has also demonstrated cytotoxicity against cancer cell lines and antimicrobial activities. Marine fungi can produce high amounts of bioactive compounds. So, a screening was performed to study sterol composition using GC/MS in 19 marine fungal strains and ergosterol was always the major one. One strain, Clonostachys rosea MMS1090, was selected due to its high amount of eburicol and a one strain many compounds approach was performed on seven culture media to optimize its production. After purification and structural identification by NMR, eburicol was assessed against four cancer cell lines, MCF-7, MDA-MB-231, NSCLC-N6-L16 and A549, and seven human pathogenic bacteria Staphylococcus aureus, Bacillus sp., Bacillus cereus, Listeria ivanovii, Escherichia coli, Citrobacter freundii and Salmonella spp. The most significant activity was cytotoxicity against MCF-7 cells (2 µM). This is the first report of such an accumulation of eburicol in the marine fungal strain C. rosea confirming its potential in the production of bioactive lipids.